Effects of Fermentated Feed and Probiotic + Acidifier Supplements on Glucose Levels and Abdomen Chicken Fat Broiler - Askura Nikmah; Fita Ridhana; Ilma Fitri; Hikmah Hikmah (Budapest International Research and Critics University, 2021)
The purpose of this study was to determine the effect of adding probiotic acidifier on the condition of the digestive tract, glucose levels and abdominal fat in broiler chickens. This research conducted in Takengon, Central Aceh District. The parameters observed were the condition of the digestive tract, blood glucose levels and the percentage of abdominal fat. The data obtained were analyzed using analysis of variance (ANOVA). The results showed the use of a 1: 1 mixture of probiotics and acidifier to level 0. The 3% added to the commercial ration which was substituted with 10% fermented feed ingredients (R-KFPA) had no significant effect (P <0.05) on weight and percentage of Gizzard, Gizzard pH and Intestine pH, Intestinal Length, Weight and Percent of Abdominal Fat, as well as blood glucose levels in broiler chickens. Although statistically not significantly different, giving a mixture of probiotics and acidifier at the level of 0.3% (R4) showed a positive effect on decreasing the percentage of abdominal fat from 1.52% (R1) to 1.35% (R4). The blood glucose obtained in this study was slightly higher than normal blood glucose levels in chickens as reported by Swenson weight and percentage of abdominal fat, as well as blood glucose levels of broiler chickens. Although statistically not significantly different, giving a mixture of probiotics and acidifier at the level of 0.3% (R4) showed a positive effect on decreasing the percentage of abdominal fat from 1.52% (R1) to 1.35% (R4). The blood glucose obtained in this study was slightly higher than normal blood glucose levels in chickens as reported by Swenson weight and percentage of abdominal fat, as well as blood glucose levels of broiler chickens. Although statistically not significantly different, giving a mixture of probiotics and acidifier at the level of 0.3% (R4) showed a positive effect on decreasing the percentage of abdominal fat from 1.52% (R1) to 1.35% (R4). The blood glucose obtained in this study was slightly higher than normal blood glucose levels in chickens as reported by Swenson (1993), which ranges from 13 to 27 ml / dl or 130 to 270 mg / dl. It is suspected that this is due to increased digestive activity in chickens so that more nutrients are absorbed.